2015
DOI: 10.1002/pssr.201510258
|View full text |Cite
|
Sign up to set email alerts
|

Thermally‐activated post‐growth dewetting of fullerene C60 on mica

Abstract: Understanding and controlling the growth and stability of molecular thin films on solid surfaces is necessary to develop nanomaterials with well‐defined physical properties. As a prominent model system in organic electronics, we investigate the post‐growth dewetting kinetics of the fullerene C60 on mica with real‐time and in situ X‐ray scattering. After layer‐by‐layer growth of C60, we find a thermally‐activated post‐growth dewetting, where the smooth C60‐layer breaks up into islands. This clearly shows that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In contrast to CuPc, the post-growth roughness of C60 thin films increases when the substrate is heated during growth. It was shown that C60 molecules react to substrate heating by island formation due to a molecular upward diffusion 95 , which explains the enhanced roughness at 400 K found in the present study. This effect is well reproduced by the simulation, see Fig.…”
Section: C60supporting
confidence: 68%
See 2 more Smart Citations
“…In contrast to CuPc, the post-growth roughness of C60 thin films increases when the substrate is heated during growth. It was shown that C60 molecules react to substrate heating by island formation due to a molecular upward diffusion 95 , which explains the enhanced roughness at 400 K found in the present study. This effect is well reproduced by the simulation, see Fig.…”
Section: C60supporting
confidence: 68%
“…The random orientation of C60 crystals on native silicon oxide and the formation of islands at a very early stage of growth (as it will be discussed in Sec. IV) is in contrast to the growth of C60 on mica 94,95 . It seems that the molecule-substrate interaction plays a crucial role in thin film growth and was therefore considered as one of the main parameters in the simulations.…”
Section: Experimental Evidence Of Phase Separationmentioning
confidence: 87%
See 1 more Smart Citation
“…Studies on other molecules such as buckminsterfullerene, C 60 , report the opposite behavior of film roughening during growth on heated substrates (Bommel et al, 2015), which could be due to different molecular shapes and interaction energies. The spherical shape of C 60 molecules does not support a special growth direction.…”
Section: Discussionmentioning
confidence: 99%
“…This journal is © the Owner Societies 2016 model step-edge effects in anisotropic (multilayer) growth morphologies on experimental scales. [67][68][69]…”
mentioning
confidence: 99%